Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3106/041.041.0303
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Coat-Color-Controlling Genes,Mc1randAsip, in the House MouseMus musculusfrom Madagascar

Abstract: Abstract. Variability in the coat color of the house mouse, Mus musculus, provides an opportunity to study the evolution of phenotypes in this species. Here we associated genetic variations with coat color in seven mice from Madagascar that had identical M. m. gentilulus mitochondrial DNA sequences. The entire coding region of the 948-base pair (bp) coat-color-related gene, Mc1r, was shown to have no nonsynonymous changes. However, analyses of the two exon-1 promoter regions-termed 1A (317 bp) and 1B (499 bp)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Interestingly, the origin of Malagasy is constructed by Southeast Asia and East Africa based on Y-chromosomal sequences [ 45 ]. On the other hand, the house mouse, Mus musculus , in Madagascar is similar to the Yemen linage, suggesting that the Madagascar lineage was introduced from Yemen in Arabian Peninsula [ 46 ]. The precise origin of R. rattus in Madagascar is still unclear, but it may be associated with the peopling of Madagascar from Southeast Asia and Indonesia [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the origin of Malagasy is constructed by Southeast Asia and East Africa based on Y-chromosomal sequences [ 45 ]. On the other hand, the house mouse, Mus musculus , in Madagascar is similar to the Yemen linage, suggesting that the Madagascar lineage was introduced from Yemen in Arabian Peninsula [ 46 ]. The precise origin of R. rattus in Madagascar is still unclear, but it may be associated with the peopling of Madagascar from Southeast Asia and Indonesia [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…DOM currently has a wide distribution covering Africa, Oceania and North and South America and can be easily introduced anywhere in the world (e.g., Gabriel et al 2011). Five distinct lineages of mitochondrial DNA (mtDNA) exist in M. musculus (Prager et al 1998;Sakuma et al 2016), three of which represent the three major subspecies groups of MUS, DOM and CAS and two of haplotypes from limited geographic areas in Nepal (Terashima et al 2006) and Yemen and Madagascar (Duplantier et al 2002), respectively. The three major subspecies lineages contain substantial levels of divergence within each of them.…”
Section: Introductionmentioning
confidence: 99%
“…The mtDNA analysis revealed that the Yemeni house mouse mtDNA lineage forms a cluster of another potential subspecies, M. m. gentilulus (GEN), which is distinct from the three major subspecies (Prager et al ., 1998; Suzuki et al ., 2013). The mtDNA lineage in Madagascar constitutes a “narrow” monophyletic group, suggesting a recent and probably single origin (Duplantier et al ., 2002; Sakuma et al ., 2016). Suzuki et al (2013) further showed that the Madagascar-Yemen mitochondrial lineage was in the most basal place to M. musculus .…”
Section: Introductionmentioning
confidence: 99%